Futile trauma transfers: An infrequent but costly component of regionalized trauma care. Issue 1 (July 2021) - Follette, Craig; Halimeh, Bachar; Chaparro, Annelise; Shi, Alan; Winfield, Robert
Abstract : BACKGROUND: Appropriate interfacility transfers are a key component of highly functioning trauma systems but transfer of unsalvageable patients can overburden the resources of higher-level centers. We sought to identify the occurrence and associated reasons for futile transfers within our trauma system. METHODS: Using prospectively collected data from our system database, a retrospective cohort study was conducted to identify patients who underwent interfacility transfer to our American College of Surgeons level I center. Adult patients from June 2017 to June 2019 who died, had comfort measures implemented, were discharged, or went to hospice care within 48 hours of admission without significant operation, procedure, or radiologic intervention were examined. Futility was defined as resulting in death or hospice discharge within 48 hours of transfer without major operative, endoscopic, or radiologic intervention. RESULTS: A total of 1, 241 patients transferred to our facility during the study period. Four hundred seven patients had a length of stay less than or equal to 48 hours. Eighteen (1.5%) met the criteria for futility. The most common reason for transfer in the futile population was traumatic brain injury (56%) and need for neurosurgical capabilities (62%). Futile patients had a median age and Injury Severity Score of 75 and 21. The main transportation method was ground 9 (50%) with 8 (44.4%) being transported by helicopter and 1 (5.6%) being transported by both. Combining transport costs with hospital charges, each futile transfer was estimated to cost US $56, 396 (interquartile range, 41, 889–106, 393) with a total cost exceeding US $1.7 million. With an estimated 33, 000 interfacility transfers annually for trauma in the United States, the cost of futile transfers to the American trauma system would exceed 27 million dollars each year. CONCLUSION: Futile transfers represent a small but costly portion transfer volume. Identification of patients whose conditions preclude the benefit of transfer due to futility and development of appropriate support for referral will significantly improve appropriate allocation of health care resources. LEVEL OF EVIDENCE: Economic; Care management, level IV.